2016
DOI: 10.1007/jhep09(2016)103
|View full text |Cite
|
Sign up to set email alerts
|

Melnikov’s method in String Theory

Abstract: Melnikov's method is an analytical way to show the existence of classical chaos generated by a Smale horseshoe. It is a powerful technique, though its applicability is somewhat limited. In this paper, we present a solution of type IIB supergravity to which Melnikov's method is applicable. This is a brane-wave type deformation of the AdS 5 ×S 5 background. By employing two reduction ansätze, we study two types of coupled pendulum-oscillator systems. Then the Melnikov function is computed for each of the systems… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Although chaos in string motion has been studied [11][12][13][14][15][16][17][18][19][20][21] in curved geometries, in view of the chaos bound (1), two important issues are left unsolved: First, the motion of the string needs to be near the black hole horizon, and second, the CFT interpretation of the string motion is indispensable. In this paper we address these two issues, by adopting a suspended string in the AdS black hole geometry.…”
Section: Introductionmentioning
confidence: 99%
“…Although chaos in string motion has been studied [11][12][13][14][15][16][17][18][19][20][21] in curved geometries, in view of the chaos bound (1), two important issues are left unsolved: First, the motion of the string needs to be near the black hole horizon, and second, the CFT interpretation of the string motion is indispensable. In this paper we address these two issues, by adopting a suspended string in the AdS black hole geometry.…”
Section: Introductionmentioning
confidence: 99%
“…By computing the power spectrum, Lyapunov characteristic exponents and Poincaré sections, in [10] it was shown that the motion of classical circular strings in the AdS 5 -Schwarzschild background is chaotic. This was subsequently extended to a wide range of backgrounds such as the AdS soliton background [11], AdS 5 ×T 1,1 [12], other AdS 5 × Einstein 5 spaces [13] and p-brane backgrounds [14][15][16], see also . Moreover, the string motion in the gravity dual of β-deformed N = 4 SYM theory was shown to be chaotic for imaginary values of β [39].…”
Section: Introductionmentioning
confidence: 99%
“…So most wellknown in AdS/CFT have nonintegrable string dynamics: AdS-Schwarzschild, AdS-Reissner-Nordstrom, AdS soliton and AdS-Sasaki-Einstein. 4 Other results on (non)integrability can be found in [29][30][31][32]; the list is not exhaustive. Apart from the usual spherical static black holes (neutral and charged), we consider also non-spherical horizons with constant curvature.…”
Section: Introductionmentioning
confidence: 99%